The Strategy Exploration To Improve Corporate Accelerator (CA) Performance: Case study on Metranet as a subsidiary of Telkom Group - Mutiara; Ghina, Astri (Integrasi Sains Media, 2025)
In Indonesia, digital startups play a vital role as drivers of innovation across sectors. Pro-technology regulations and a strong entrepreneurial mindset support their growth. PT Metra-Net, a subsidiary of Telkom Indonesia, operates a Corporate Accelerator (CA) program; however, its performance from 2019 to 2023 has not met expectations. This study aims to evaluate the factors influencing CA performance and formulate strategies for improvement. A qualitative case study approach was employed, with data collected through in-depth interviews and documentation, and analysed using Miles & Huberman's model. The theoretical framework comprises an internal analysis (IFE) based on the Resource-Based View (RBV) and an external analysis (EFE) utilising the PESTLE framework and Porter's Five Forces. Findings reveal Metranet's key strengths lie in access to the Telkom Group ecosystem and a collaborative management structure. Weaknesses include low go-to-market (GTM) synergy, limited research and development (R&D) capabilities, and underutilised data. External challenges arise from regulatory changes and global competition. Based on SWOT and IE Matrix analysis, an aggressive (growth-oriented) strategy is recommended. Improving CA performance requires aligning internal strategies with adaptive responses to external challenges. Recommendations include strengthening the CIO's role, optimising ESG and AI-driven R&D, and aligning with the digital market needs of state-owned enterprises (BUMN).